PELATIHAN DAN PENYULUHAN PEMBUATAN BRIKET SAMPAH PLASTIK UNTUK KARANG TARUNA DI TPS 3R ”PONCO BANYAK” DI DESA MANTREN KARANGREJO MAGETAN - Rachman, Natriya Faisal; Zainul Arifin, Muhammad; Oktavia, Wahyuni; Kustanto, Jaka Septian; Surlitasari Dewi, Desi (Madiun Spoor : Jurnal Pengabdian Masyarakat, 2024)
Environmental problems due to the lack of effective waste management have become a serious challenge in this modern era, triggering air, land, and water pollution and damaging ecosystems. triggering air, soil, and water pollution and damaging ecosystems. Waste is piling up not only in urban areas but also in rural areas due to population growth, urbanization, and increasing consumption patterns. approach 3Rs (Reduce, Reuse, Recycle) approach has become urgent to reduce dependence on landfills and minimize the impact of landfills. on landfills and minimize negative environmental impacts. Village Mantren adopted this approach by establishing the 3R TPS "Ponco Banyak" TPS 3R in 2022, which serves more than 500 homes and several customers outside the village. customers outside the village. In addition to waste collection, TPS 3R also composts and makes briquettes from recycled materials. making briquettes from recycled materials. Through systematic training and counseling training and counseling, the program increased community awareness and knowledge about 3R practices, making Karang Taruna members more knowledgeable about waste management and having the skills to make recycled products such as briquettes. waste management and have the skills to make recycled products such as briquettes that can be marketed, making Mantren Village marketable, making Mantren Village an example of sustainable waste management. sustainable waste management.